Dorian Unmaking Space: Policy, Place and Dislocation - Bethell-Bennett, Ian A. (International Journal of Bahamian Studies, 2021)
Within an autoethnographic approach, this paper employs concepts such as spatial and climate (in)justice and structural and slow violence to explore disaster capitalism that results from a neoliberal state and its desire to dispose of people it deems as being less worthy. Focusing on the impacts of Hurricane Dorian on Abaco and the fallout, this work builds on other disasters in the region and attempts to draw parallels between the Bahamian government’s response to Hurricane Dorian and the similarity this response shares with other regional reactions to natural disasters.